Antecedents of Cloud Accounting Adoption and Its Consequences on SME Performance: A TOE Framework Approach - Parasdya Pandhu Andanawarih; Shofiatul Mila; Dian Novitaningrum (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpose of this research is to investigate the factors that influence the adoption of cloud accounting, including relative benefit, complexity, support from top management, organizational preparedness, competitive pressure, bandwagon effect, computer self-efficacy, and computer anxiety., as well as its impact on MSME performance in Kendal Regency. The study in question takes a quantitative approach and makes use of primary data gathered via the use of questionnaires. A purposive sampling method was used to pick 250 respondents from micro, small, and medium-sized enterprises (MSMEs) in the Kendal Regency. The research makes use of the Structural Equation Modeling (SEM) technique in conjunction with the Partial Least Squares (PLS) methodology. According to the findings, the adoption of cloud accounting is favorably influenced by factors including as support from senior management, competitive pressure, the bandwagon effect, and user confidence in their ability to use IT. The implementation of cloud accounting has a favorable and substantial influence on the performance of micro, little, and medium-sized enterprises (MSME). With that being said, relative advantage, complexity, organizational readiness, and computer anxiety negatively influence cloud accounting adoption. This research makes a contribution to the TOE framework by highlighting the significance of technical, organizational, and environmental factors readiness alongside individual support in adopting cloud accounting to improve MSME performance. Practically, the Kendal Regency government is expected to take a more active role in providing stimuli regarding the importance of digital transformation to enhance MSME performance.